Comparative efficacy of levamisole and fenbendazole in the treatment of ewes before lambing - Tyrer, Margaret Jane (The University of Edinburgh, 1977)
This project was undertaken to ascertain the effects of two anthelmintics, levamisole and fenbendazole, when given to ewes six weeks before lambing. The investigation involved three flocks of sheep of different breeds, Suffolk, crossbred Suffolk and Cheviot; which lambed in January, April and March respectively. Faecal egg counts of the ewes were recorded regularly between November 1976 and July 1977. Nematode species were identified by the measurement of egg dimensions and the observation of development when incubated for seven days at 4.5°C. Serum pepsinogen values were used as a further measure of the nematode infection. In all three flocks, both drugs suppressed nematode egg excretion for several weeks. Although treatment had a significant effect in individual uses in depressing the rise in the faecal egg count associated with lambing and significantly delayed the rise in the January lambing ewes and in a housed section of the April lambing ewes, it did not significantly depress total egg output in any flock over the period of the rise. The rise in the January flock was post-parturient, whereas a peri-parturient rise occurred in both the later lambing flocks. This may indicate that maturation of inhibited Ostertagia species was of greater importance in the January flock: that their rise was higher lends further support to this theory. The failure of either anthelmintic to effectively suppress the rise was attributed largely to reinfection in the January flock and to the inability of the drug to remove inhibited larvae in the other two flocks. This was supported by findings in ewes housed soon after dosing. Eggs of Ostertagia spp. predominated in all flocks during the rise; this reflects the ability of this genus to survive over winter both on pasture and as inhibited larvae in the sheep. Sixteen lambs born into the January flock and 533 lambs from the March lambing flock were weighed to measure any increase in live-weight gain which may be due to pre-lambing treatment of the ewes. No significant differences were found. It was therefore concluded that there was no production benefit gained by the pre-lambing dosing of the ewes with either fenbendazole or levamisole when they were returned to contaminated pasture.
The comparative efficacy of levamisole and fenbendazole in the treatment of ewes before lambing
Keywords: Annexe MSc Digitisation Project 2022 Block 39